The circadian code : lose weight, supercharge your energy, and transform your health from morning to midnight - Panda, Satchin (Rodale, 2018)
A comprehensive health book and lifestyle plan to help manage the body's natural rhythms offers advice to overcome difficulty sleeping, hunger at odd times, and sudden fatigue.